Environmental DNA from peck marks shows potential for non‑invasive monitoring of woodpeckers. - Muhammad Bilal Sharif; Björn Ferry; Jérôme Fuchs; Bodil Cronholm; Peter D Heintzman; Love Dalén (PLoS ONE)
Monitoring species' occurrences is essential for understanding ecosystem dynamics, tracking biodiversity changes, and guiding conservation efforts. Traditional monitoring methods, such as visual surveys, are challenging, particularly for elusive and endangered species. This proof-of-concept study explores the potential of environmental DNA (eDNA) collected from peck marks as a non-invasive tool for detecting and identifying woodpecker species. We collected nine samples from fresh peck marks on birch and spruce trees in the forests of Swedish Lapland. In two samples, we successfully amplified an 81 base-pair fragment of the woodpecker mitochondrial 16S rRNA gene. Taxonomic assignment identified the Eurasian three-toed woodpecker (Picoides tridactylus), a species classified as "Near Threatened" in Sweden. We collected an additional 15 samples from 4-19 years old peck marks preserved inside the trunks of birch and pine trees in the same area. No woodpecker DNA was detected in these samples, likely due to DNA degradation. Our findings demonstrate the potential of using eDNA from peck marks as a non-invasive approach for monitoring elusive woodpecker species.